Pengaruh Campuran Bioethanol Kapur Barus pada Bahan Bakar Pertamax terhadap Kadar Emisi Gas HC - Arrozi, Zulfan Maulana; Listiyono, Listiyono (Lembaga Yasin AlSys, 2024)
Fuel plays an important role in vehicle performance, and octane rating is one of the main factors. One innovation is to blend the fuel with additives such as bioethanol that can increase octane and reduce emissions of pollutants such as CO, CO2, HC, and NOx. This study examines the use of an affordable and readily available blend of bioethanol and camphor as an alternative fuel. In addition, this study also aims to determine the most effective blend variation to reduce exhaust emissions. This study uses an experimental method by manipulating one or more independent variables and measuring their effect on the dependent variable. The independent variables in this study are 10%, 15%, and 20% bioethanol mixture and camphor 5 grams, 10 grams, and 15 grams in Pertamax. As for the dependent variable is the exhaust gas content with variations in engine speed of 1500, 3000, and 4500 rpm. The study data were then presented in tabular form and analyzed using the two-way analysis of variance (ANOVA Two Way) method along with the data graph. The results showed a decrease in CO levels by 19.51% at 1500 RPM and 84.13% at 3000 RPM and a decrease in HC by 37.44% at 1500 RPM and 48.68% at 4500 RPM.